EFFECTIVENESS OF CREATIVE PRODUCT LEARNING AND ENTREPRENEURSHIP OF THE LIGHT VEHICLE ENGINEERING PROGRAMME AT SMK NEGERI 1 BINTAN UTARA - Fitria Destika Wulandary; Sumarno; Hendripides (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the effectiveness of creative product learning and entrepreneurship in the light vehicle engineering programme at Class XII of SMK Negeri 1 Bintan Utara. The method the researchers used was a quantitative descriptive method with a formative evaluation model. The research object was creative product learning and entrepreneurship of class XII. Data collection techniques used tests and observation. Data were analyzed descriptively. The results imply that the presentation for the learning process was 72.5% and students’ learning outcome was 53.85%. Thus, it can be concluded that (1) the creative products and entrepreneurship learning process in the light vehicle engineering program at SMK Negeri 1 Bintan Utara is still in the sufficient category, (2) students’ learning outcome of creative products and entrepreneurship in the light vehicle engineering program at SMK Negeri 1 Bintan Utara is still in the less category, and (3) the effectiveness of creative product learning and entrepreneurship in the light vehicle engineering program at SMK Negeri 1 Bintan Utara is still not effective.